AJVR Reviewers, 2012 (American Journal of Veterinary Research, 2013)
OBJECTIVE: To present clinical features, CT findings, treatment, and outcome for traumatic jaw fractures diagnosed via CT. ANIMALS: Medical records from 2014 through 2026 were reviewed, and 21 rabbits with traumatic jaw fractures diagnosed by CT were selected. CLINICAL PRESENTATION: Among the 21 rabbits that fit the inclusion criteria, trauma sources included involuntary owner-inflicted trauma (n = 10), sofa-related falls or entrapment (3), dog bites (2), post-dental trimming issues (1), trauma with a table (1), fall of cardboard onto the head (1), fall of a folding table onto the head (1), and unknown (2). RESULTS: Fractures of the mandibular ramus were identified in 85.7% cases (unilateral, n = 14; bilateral, 4). Concurrent fractures were common (intermandibular suture (n = 5), body of the mandible (4), zygomatic arch (5), frontal bone (1), presphenoid bone (1), tympanic bulla (1)). A recurrent mandibular fracture pattern was seen in 47.6% of cases (n = 10). Complications in 13 rabbits that had a follow-up included dental malocclusion of incisors (n = 8) and cheek teeth (6), chronic dacryocystitis (2), hyperthermia (2), mandibular abscess (1), and persistence of vestibular syndrome (1). Notably, 11 rabbits were still alive 581 days after the trauma. CLINICAL RELEVANCE: Traumatic jaw injuries in rabbits frequently involve multiple concurrent fracture sites and associated craniofacial lesions. Computed tomography allowed detailed anatomical characterization of fracture configurations and associated injuries, supporting its value for comprehensive lesion assessment. Mandibular ramus fractures were the most common injuries and were generally associated with favorable survival, although long-term dental complications were frequent.